Lithuanian book publishing during World War I - Vanda Stonienė (Knygotyra)
The development of Lithuanian book publishing was severely hampered during World War I. In 1915, Lithuania was occupied by German military forces, and no activities of cultural institutions were allowed without permission from the occupiers.